The Distributional Implications of Pension Benefit Indexation - Torben M. Andersen; Cecilie Marie Løchte Jørgensen (Center for Economic Studies and ifo Institute (CESifo), 2024)
Socio-economic differences in longevity have fuelled a debate whether pension systems have a regressive bias favouring groups with a high life expectancy. We show that the distributional implications of such pooling depend critically on the benefit profile across age/time, which in turn is determined by how benefits are indexed to prices and wages. Choosing indexation scheme involves a choice between a low initial benefit with an increasing profile and a high initial benefit with a flat/decreasing profile, where the former benefits groups with a high life expectancy, and vice versa. We analyse how indexation affects the trade-off between insurance and distribution when groups with different mortality are separated or pooled, and the optimal benefit profile under both standard preferences and temporal risk aversion wrt. the length of life.
Keywords: D14; G22; H55; J18; 330; annuities; differential mortality; distribution; indexation